Effect of Er: YAG Laser on Microtensile Bond Strength of Bleached Dentin to Composite - Rezaei, Mohsen; Aliasghar, Elham; Rezvani, Mohammad Bagher; Chiniforush, Nasim; Moradi, Zohreh (Journal of Lasers in Medical Sciences, 2019)
Introduction: In non-vital tooth bleaching, dentin is in direct contact with the bleaching agent, 1 to 3-week delay is needed to eliminate free radicals from tooth structure. The present study aimed to evaluate the effect of irradiation of Er: YAG laser on immediate microtensile bond strength of bleached dentin to composite. Methods: Sixty sounds human teeth were collected and randomly divided into 4 groups (n = 15): no bleaching (NB), opalescence endo hydrogen peroxide (HP) gel bleaching, sodium perborate (SP) bleaching and laser bleaching with heydent gel (LB). The groups were divided into 3 subgroups (n = 5): no surface treatment, Er: YAG laser irradiation and 10% sodium ascorbate (SA). All samples were restored and underwent microtensile bond strength testing. Statistical analysis was carried out using one-way and two-way ANOVA. Results: Bond strength in NB-SA group had a significant difference with the NB group (P < 0.05) while no significant difference was noted between NB and NB-Er groups (P = 0.55). Application of SA and Er: YAG laser after bleaching with SP did not enhance the bond strength (P = 0.07). Conclusion: Application of SA and Er: YAG laser after HP gel bleaching significantly enhanced the bond strength. Application of Er: YAG laser after internal bleaching with HP gel could enhance the bond strength.